A combination of chain and neurophilic migration involving the adhesion molecule TAG-1 in the caudal medulla. - Kyriakopoulou, Katerina; De-Diego-Barbado, Isabel; Wassef, Marion; Karagogeos, Domna (Wiley, 2002)
TAG-1 está involucrada en la emigración de elas células destinadas a los núcleos precerebelares durante el desarrollo embrionario

Neuronal populations destined to form several precerebellar nuclei are generated by the rhombic lip in the caudal hindbrain. These immature neurons gather into the olivary and the superficial migratory streams and migrate tangentially around the hindbrain to reach their final position. We focus on the cells of the superficial stream that migrate ventrally, cross the midline and form the lateral reticular (LRN) and external cuneate (ECN) nuclei. The cells of the superficial steam are preceded by long leading processes; in the dorsal neural tube, they migrate in close apposition to each other and form distinct chains, whereas they disperse and follow Tuj-1 immunoreactive axons on reaching the ventral hindbrain. This suggests that, in the superficial stream, neuronal migration combines both homotypic and heterotypic mechanisms. We also show that the adhesion molecule TAG-1 is expressed by the migrating cells. Blocking TAG-1 function results in alterations in the superficial migration, indicating that TAG-1 is involved in the superficial migration. Other members of the immunoglobulin superfamily and known ligands of TAG-1 are also expressed in the region of the migration but are not involved in the migration. These findings provide evidence that the TAG-1 protein is involved as a contact-dependent signal guiding not only axonal outgrowth but also cell migration.
https://openpolicyfinder.jisc.ac.uk/id/publication/14668
Keywords: Embriología; Glucoproteínas; Médula espinal; Desarrollo neurológico; Migration; Caudal medulla; TAG-1